Institutional Factor Analysis on the Sustainability of Community-Based Drinking Water Infrastructure in Sidenreng Rappang District - Muslimin, Muslimin; Andi Sinrang; Erfina, Erfina (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze institutional factors affecting the sustainability of community-based drinking water infrastructure in Sidenreng Rappang District. The research was conducted in 31 villages/wards that are part of the Pamsimas Program locations. The survey was carried out using a purposive sampling method involving 62 respondents, consisting of members of the Drinking Water Supply Management Group (KP-SPAMS) and beneficiary community members. The study employed quantitative methods with SPSS (Statistical Package for the Social Sciences) as a statistical tool. The SPSS output shows that the t-test value for the institutional variable (X2) is t = 4.282 with a significance value of 0.000 < 0.05. This indicates a partial influence of institutional factors on infrastructure sustainability. The standardized beta value also shows that institutional factors (X2) significantly influence the program’s sustainability, and among all variables, institutional factors have the highest B value, indicating they are the most dominant factor affecting the sustainability of drinking water infrastructure under the Pamsimas Program in Sidenreng Rappang District.